2020
DOI: 10.1111/dth.14507
|View full text |Cite
|
Sign up to set email alerts
|

Treatment considerations for Behçet disease in the era of COVID ‐19: A narrative review

Abstract: COVID‐19 is a multisystem disease caused by severe acute respiratory syndrome coronavirus 2. It has been declared a pandemic by the World Health Organization in March 2020 and the outbreak still keeps its impacts worldwide. Behçet disease (BD) is a multi‐systemic vasculitis involving the skin, mucosa, eyes, joints, nervous system, cardiovascular system, and gastrointestinal system. The precise etiopathogenesis of the disorder is unknown but autoimmunity is believed to play a key role. A considerable part of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Considering their potential beneficial effects on the course of COVID-19; colchicine, pentoxifylline, and dapsone can be considered as safe treatment options where indicated in BD. However, their role needs further evaluation ( 140 ). A retrospective analysis conducted by Bolletta et al showed that despite immunosuppression (or some patients having stopped treatment) along with Covid-19 infection in Behçet patients, few of their cohort required hospitalization, none was admitted to the ICU and eventually about one third had exacerbation in at least one of their BD-related symptoms ( 141 ).…”
Section: Behçet's Uveitis and Covid-19mentioning
confidence: 99%
“…Considering their potential beneficial effects on the course of COVID-19; colchicine, pentoxifylline, and dapsone can be considered as safe treatment options where indicated in BD. However, their role needs further evaluation ( 140 ). A retrospective analysis conducted by Bolletta et al showed that despite immunosuppression (or some patients having stopped treatment) along with Covid-19 infection in Behçet patients, few of their cohort required hospitalization, none was admitted to the ICU and eventually about one third had exacerbation in at least one of their BD-related symptoms ( 141 ).…”
Section: Behçet's Uveitis and Covid-19mentioning
confidence: 99%
“… 1 The pathogenesis is unclear but it has been established that immunological aberrations might play a main role in the BD development. 2 To date, there is limited evidence regarding the susceptibility and severity of Covid-19 infection is patients displaying BD 3 , 4 and only case series studies have explored the characteristics and outcomes of BD patients with Covid-2019. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Among one of the most common known side effects are viral upper respiratory infections.With the COVID-19 outbreak, questions about disease-related immunosuppression and treatments in autoinflammatory diseases such as ABD have been posed. Elmas et al16 reviewed the recommendations from task force of the American College of Rheumatology, the European League Against Rheumatism and the International Society for Behçet disease stating that there is no reason to discontinue topical treatments, colchicine, and nonsteroidal anti-inflammatory drugs. Systemic steroids should be used at the lowest possible dose if needed and ongoing treatments can be continued unchanged in patients with no suspected or confirmed COVID-19 infection 16.…”
mentioning
confidence: 99%
“…Elmas et al16 reviewed the recommendations from task force of the American College of Rheumatology, the European League Against Rheumatism and the International Society for Behçet disease stating that there is no reason to discontinue topical treatments, colchicine, and nonsteroidal anti-inflammatory drugs. Systemic steroids should be used at the lowest possible dose if needed and ongoing treatments can be continued unchanged in patients with no suspected or confirmed COVID-19 infection 16. In patients with COVID-19 symptoms, immunosuppressive and targeted drugs can be temporarily suspended, but the decision should be made on a case-by-case basis considering the potential beneficial effects on the course of COVID-19.…”
mentioning
confidence: 99%
See 1 more Smart Citation